Government Cooperation In Malang City And Malang Regency Government In Management Water Resources Wendit - Eka, Elly; Syafrieyana, Yana; Kamil, Muhammad (Government Studies of Muhammadiyah Malang University/AIPPTM, 2019)
The increase in population is 0.9% each year. It affects the amount of water demand in Malang City. From 2014 to 2016 the water demand in Malang City reached 30,364,684m³. This is a balanced water source production in Malang City, which is around 11.7% of the total water source in the Greater Malang region. Therefore, cooperation between a cooperation agreement from 2002 to 2022. The cooperation between Malang Regency Government and Malang City Government. The research method used for Wendit Resources and the problems is a descriptive approach to the management of Wendit Resources. Data collection techniques are carried out by observation, interviews, and documentation. The theory used is Intergovernmental Networks Robert Agranoff which emphasizes the existence of key actors and joint actions in implementing cooperation. The results of the study show that there are action networks in the implementation of cooperation and management of Wendit Resources. Malang Regency Government as a water source provider and Malang City Government utilizes and manages the water source to meet water needs in Malang City. The problem in cooperation is the existence of disputes over the cost of contributions between the two regions and less intense coordination between the two regions.